Potensi Limbah Blotong PG. Krebet Sebagai Bahan Baku Produksi Biogas Dalam Upaya Pengembangan Industri Terintegrasi - Sasongko , Pramono ; Tantalu , Lorine (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Krebet Sugar Factory (PG) located in Bululawang Malang, East Java is one of the large-scale sugar processing industries. It produces large amounts of sugar cane filter cake (437 Ton / day). Sugar cane filter cake containing organic compound such as C, H, and O. However, the utilization of sugar cane filter cake still low. Since it included in the category of organic waste then it potentially to be utilized as biogas raw material through anaerobic fermentation process. Therefore the research to determine optimum conditions of fermentation is urgently needed. In order to be part of that purposes this study aimed to obtained characteristic of sugar cane filter cake from Krebet Sugar factory and make established a small-scale fermentor. The result of the preliminary research were shown thath by using a 3 kilogram fermentor the methane gas or biogas produced in 21 days of fermentation. In order to optimize the rate of gas production fermentor scale up is needed. Therefore, a 20 kilogram scale fermentor was builded completed with a gas volume measuring and gas flame test devices. Based on those result sugar cane filter cake from Krebet Sugar Factory has promising result to be processed to be a biogas.. In addition, it can provide an alternative energy option for the factory in the implementation of Clean Production and provide opportunities to increase the efficiency production.